Statistical evaluation of the similarity of characteristics in springs of the California Desert, United States - Love, Adam H.; Zdon, Andy; Fraga, Naomi S.; Cohen, Brian; Palacios Mejia, Maura; Maxwell, Rachel; Parker, Sophie S. (Frontiers in Environmental Science, 2022)
Desert ecosystems are an environment of climatic extremes, to which many forms of life have adapted. These systems are characterized by scarce water and often sparsely vegetated lands where ecological adaptation to arid conditions has its underpinnings in the universal dependency on water to support life. Understanding the ecohydrological similarity of springs in water-limited areas requires integration of multiple lines of evidence from diverse disciplines. A unique dataset of hydrological and ecological characteristics of Mojave and Sonoran Desert spring ecosystems in California has been developed, incorporating a wide range of spring conditions that enables a broad evaluation of similarity in ecohydrological characteristics across springs in the region. The lack of observed correlation between hydrologic and ecological parameters suggests that the springs in the California Desert each represent a somewhat unique ecosystem that has developed in relative isolation from the other springs. These results imply that because of the uniqueness of these desert ecosystems the idea of mitigation compensation or mitigation offset via replacement or substitution can never truly be achieved if/when these spring areas are impacted. Any ecosystem used as a replacement or substitution could not reasonably be expected to be similar in terms of the associated hydrologic and ecologic conditions to the ecosystem lost. While such offsets can represent a coarser view of replacements or substitution, the more specific conditions that support endemic and water-dependent biodiversity cannot be easily replaced or substituted.